Characterization and Establishment of a Novel EBV Strain Simultaneously Associated With Nasopharyngeal Carcinoma and B-Cell Lymphoma - Yu, Fenggang; Syn, Nicholas L.; Lu, Yanan; Chong, Qing Yun; Lai, Junyun; Tan, Wei Jian; Goh, Boon Cher; MacAry, Paul A.; Wang, Lingzhi; Loh, Kwok Seng (Frontiers in Oncology, 2021)
Epstein-Barr virus (EBV) – the prototypical human tumor virus – is responsible for 1-2% of the global cancer burden, but divergent strains seem to exist in different geographical regions with distinct predilections for causing lymphoid or epithelial malignancies. Here we report the establishment and characterization of Yu103, an Asia Pacific EBV strain with a highly remarkable provenance of being derived from nasopharyngeal carcinoma biopsy but subsequently propagated in human B-lymphoma cells and xenograft models. Unlike previously characterized EBV strains which are either predominantly B-lymphotropic or epitheliotropic, Yu103 evinces an uncanny capacity to infect and transform both B-lymphocytes and nasopharyngeal epithelial cells. Genomic and phylogenetic analyses indicated that Yu103 EBV lies midway along the spectrum of EBV strains known to drive lymphomagenesis or carcinogenesis, and harbors molecular features which likely account for its unusual properties. To our knowledge, Yu103 EBV is currently the only EBV isolate shown to drive human nasopharyngeal carcinoma and B-lymphoma, and should therefore provide a powerful novel platform for research on EBV-driven hematological and epithelial malignancies.